Factores críticos que determinan la intención de compra en línea en el comercio electrónico mexicano (Critical factors which determine purchase online intent in the Mexican electronic commerce) - Zubirán Shetler, Sergio Rolando; López Pérez, Jesús Fabián (Facultad de Contaduría Pública y Administración U.A.N.L., 2009)
Abstract. The following article analyzes the principal factors of electronic commerce that have been explored and studied primarily in developed markets such as the United States and that have been deemed as critical actors in the development and growth of electronic transactions. Specifically, variables and latent factors of this study derive from the models of Technology Acceptance (Davis, 1989) and Diffusion of Innovations (Rogers, 2003). A summary of past empirical studies is provided deriving from the aforementioned theoretical models followed by results of an exploratory field study comprising of 39 valid observations randomly selected from within the Professional Employees Internet Users segment. The methodology used to determine the causal relationship between variables (Betas) was factor analysis (Principal Components) and structural equation modeling, specifically Smart-PLS. The study determined that perceived utility, security and compatibility variables were statistically relevant and significant in determining purchase online intent or the development of electronic commerce in the Professional Employees Internet Users Segment.